Model comparison and quantification of nitrous oxide emission and mitigation potential from maize and wheat fields at a global scale - Tesfaye, Kindie; Takele, Robel; Sapkota, Tek B.; Khatri-Chhetri, Arun; Solomon, Dawit; Stirling, Clare; Albanito, Fabrizio (The Science of the total environment, 2021)
Maize and wheat are major cereals that contribute two-thirds of the food energy intake globally. The two crops consume about 35% of the nitrogen (N) fertilizer used in agriculture and thereby contribute to fertilizer-induced nitrous oxide (N2O) emissions. Thus, estimation of spatially disaggregated N2O emissions from maize and wheat fields on a global scale could be useful for identifying emission and mitigation hotspots. It could also be needed for prioritizing mitigation options consistent with location-specific production and environmental goals. N2O emission from four models (CCAFS-MOT, IPCC Tier-I, IPCC Tier-II and Tropical N2O) using a standard gridded dataset from global maize and wheat fields were compared and their performance evaluated using measured N2O emission data points (777 globally distributed datapoints). The models were used to quantify spatially disaggregated N2O emission and mitigation potential from maize and wheat fields globally and the values were compared. Although the models differed in their performance of capturing the level of measured N2O emissions, they produced similar spatial patterns of annual N2O emissions from maize and wheat fields. Irrespective of the models, predicted N2O emissions per hectare were higher in some countries in East and South Asia, North America, and Western Europe, driven mainly by higher N application rates. The study indicated a substantial N2O abatement potential if application of excess N in the maize and wheat systems is reduced without compromising the yield of the crops through technological and crop management innovations. N2O mitigation potential is higher in those countries and regions where N application rates and current N2O emissions are already high. The estimated mitigation potentials are useful for hotspot countries to target fertilizer and crop management as one of the mitigation options in their Nationally Determined Contributions (NDCs) to the United Nations Framework Convention on Climate Change (UNFCCC). [Display omitted] •Area-scaled N2O emissions from maize and wheat fields are higher in Asia and Europe but lower in Africa and South America.•Country total N2O emissions from maize and wheat fields are greater in East and South Asia than other regions.•N2O emissions in maize and wheat fields are driven mainly by higher N application rates.•Countries with high yields of maize and wheat have lower emission intensity compared to those with low yields.•Excess nitrogen management offers huge opportunity for N2O emission reduction and achieving national mitigation targets.